(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
Lampung transmigration is a local historical event in Lampung province. Traces of the Lampung transmigration can be traced through the heritage collection at the Lampung Transmigrations Museum. The aim of this research is to find out traces of the history of Lampung transmigration through the museum collection. This research was carried out using historical research methods which included a heuristic, criticsm, interpretation, and historiography. The result of this research show that traces of the history of transmigration in Lampung can be traced through various types of relics in the Lampung Transmigration Museum. The Lampung transmigration museum holds several collections such as collections of transportations, household, economics, livelihood, art and religious collections, as well as historical and administration collection. These collections depict the lives of tranmigrant at that time.